Linguistic Characteristics of Research Article Titles in National and International ELT Journals - Jasrial, Dedi; Ramadhan, Syahrul; Mukhaiyar, Mukhaiyar; Afful, Joseph Benjamin Archibald (Journal of Languages and Language Teaching, 2024)
Researchers have extensively studied the linguistic characteristics of research article (RA) titles. However, no research has investigated RA titles viewed from research design types published in national and international English Language Teaching (ELT) journals. Thus, the present study aims to fill this gap by investigating the average word length, syntactic structure, and syntactic structure type based on research design. This study used a comparative mixed method design to analyze 120 RA titles published in 2022-2023. The average length of titles was analyzed by counting the parts of speech of the tiles, the syntactic structures of titles were analyzed using the Framework of Cheng et al. (2012), and syntactic structure types based on research design were analyzed by reading the method section of the articles. Results indicate that the average length of the RA titles was 12 words in national journals and 13 words in international journals. Nominal structure was the most used RA title type in national journals, while compound structure was the most used in international journals. Furthermore, the nominal structure was often used for experimental design in international journals, while it was often used for descriptive study design in national journals. The compound and Verb-ing phrase structures were often used for case study design in both international and national journals. In conclusion, there are important differences and similarities in RA title characteristics between the two groups of ELT journal rankings. The findings contribute to the scholarship on the contrastive aspect of titling practices in English for Publishing Purposes.